The role of Al in the reactive synthesis of porous Mo2Ti2AlC3 ceramics. Issue 23 (1st December 2021) - Zou, Haoran; Chen, Junxiao; Li, Xide; Wen, Yi; Fan, Yiquan; Liu, Yuzuo; Xiong, Lieqiang; Yang, Junsheng
Abstract: The mixed powders of TiH2, molybdenum, aluminum and graphite with molar ratios of 2/2/ n /2.85 ( n ranges from 1.0 to 1.4 mol with an interval of 0.1 mol) were used as raw material powders for this work, and a novel porous Mo2 Ti2 AlC3 was synthesized via reactive synthesis. Through systematic research on the pore structure parameters of porous Mo2 Ti2 AlC3 prepared with different aluminum content, the results show that there is a clear correlation between the aluminum content and the pore structure parameters. With the aluminum content rising from 1.0 to 1.2 mol, the viscous permeability coefficient and pore size decreased, while the porosity increased; When the aluminum content increased from 1.2 to 1.4 mol, the pore structure parameters of porous Mo2 Ti2 AlC3 displayed an opposite trend. The reasons for the evolution laws of these pore structure parameters were also discussed in depth. In addition, the pore structure forming mechanism of porous Mo2 Ti2 AlC3 ceramics during the activation reaction sintering process has been explored. This work can provide an important reference for the subsequent preparation of quaternary porous MAX phase ceramics.